Clinical and economic impact of herpes zoster vaccination in elderly in Italy. Issue 2 (1st February 2017) - Boccalini, Sara; Alicino, Cristiano; Martinelli, Domenico; Bechini, Angela; Tiscione, Emilia; Pellizzari, Barbara; Prato, Rosa; Icardi, Giancarlo; Iannazzo, Stefania; Bonanni, Paolo
ABSTRACT: Herpes zoster (HZ) is a very relevant pathology among elderly people (≥ 60 years of age), with a considerable disease burden and loss of quality of life. In the last years a new vaccine against HZ became available in Italy. Therefore, the Italian decision makers are now confronted with the decision whether that vaccination should be implemented. Pharmaco-economic analyses represent useful tools to value the feasibility of new immunization programs and their sustainability. To this aim, an ad hoc population model was developed in order to value the clinical and economic impact of HZ vaccination program for the elderly in Italy. Particularly, different immunization scenarios were modeled: vaccination of 60 years-old subjects (single cohort strategy), simultaneous vaccination of people aged 60 and 65 years (double cohort strategy) and, lastly, immunization of people aged 60, 65 and 70 years (triple cohort strategy), thus leading to the vaccination of 5, 10 and 15 cohorts during the first 5 years of the program. The mathematical model valued the clinical impact of vaccination on the number of HZ, post-herpetic neuralgia (PHN) and ophthalmic HZ. The results of the analysis show that, in Italy, a cohort-based HZ vaccination program in elderly could have a relevant impact on the reduction of clinical cases and a favorable economic profile for the National Health Service (NHS), as already foreseen in other countries. In addition, further benefits could be obtained when extending the study period beyond the 5-year horizon of our analysis.